2013
DOI: 10.3892/ijo.2013.1891
|View full text |Cite
|
Sign up to set email alerts
|

Flufenamic acid promotes angiogenesis through AMPK activation

Abstract: Abstract. Angiogenesis plays critical roles in development, tumor growth and metastasis. Flufenamic acid (FFA) is an anti-inflammatory agent known to alter ion fluxes across the plasma membrane. Its role in angiogenesis has not been fully addressed to date. Here, we report that FFA treatment promotes angiogenesis both in vitro and in vivo. Applying FFA for 12 h promoted tube formation of human umbilical vein endothelial cells (HUVECs) without affecting cell proliferation. Three angiogenesis-related genes, VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…For further investigation of intracellular mechanisms that influence SGLT-1 activity, epithelia were incubated with 3 mM AMG in the mucosal buffer solution and 10 mM glucose in the serosal buffer solution. Epithelia were preincubated with either 0.1 mM ouabain, an inhibitor of Na ϩ -K ϩ -ATPase (4); 20 M compound C, an inhibitor of AMPK (13); 20 mM 5-aminoimidazole-4-carboxamide (AICAR) (purchased from Santa Cruz Biotechnology) and 0.2 mM flufenamic acid (FFA) (purchased from Sigma-Aldrich), both known as activators of AMPK (10,18,37,45,47); or the respective solvent as control for 30 min before subjecting part of the epithelia to hypoxia. After 45 min of hypoxia, 0.2 mM phlorizin, an inhibitor of SGLT-1 (39), were added to the mucosal buffer solution and the decrease in the slope of Isc (i.e., the loss of net charge transport across the epithelium) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…For further investigation of intracellular mechanisms that influence SGLT-1 activity, epithelia were incubated with 3 mM AMG in the mucosal buffer solution and 10 mM glucose in the serosal buffer solution. Epithelia were preincubated with either 0.1 mM ouabain, an inhibitor of Na ϩ -K ϩ -ATPase (4); 20 M compound C, an inhibitor of AMPK (13); 20 mM 5-aminoimidazole-4-carboxamide (AICAR) (purchased from Santa Cruz Biotechnology) and 0.2 mM flufenamic acid (FFA) (purchased from Sigma-Aldrich), both known as activators of AMPK (10,18,37,45,47); or the respective solvent as control for 30 min before subjecting part of the epithelia to hypoxia. After 45 min of hypoxia, 0.2 mM phlorizin, an inhibitor of SGLT-1 (39), were added to the mucosal buffer solution and the decrease in the slope of Isc (i.e., the loss of net charge transport across the epithelium) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports have documented a range of beneficial effects of FFA beyond its direct anti-inflammatory activity, including its ability to promote carbonyl reductase 1 ( CBR1 ) upregulation and thereby protect against pulmonary damage induced by sepsis ( 23 ). It can also reportedly downregulate the expression of osteoclastogenesis-related genes while activating mitogen-activated protein kinase (MAPK) signaling and thereby preventing osteoporosis ( 24 , 25 ), in addition to inducing the AMP-activated protein kinase (AMPK) activation and thereby enhancing angiogenic activity in vitro and in vivo ( 26 ). The pleiotropic properties of FFA may thus offer substantial benefits to treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the knockdown of AKR1C3 overcame doxorubicin resistance by promoting autophagy in gastrointestinal cancer cells 34 . In addition, FLU, an AKR1C3 inhibitor, has been reported to activate AMPK signaling, which directly regulates autophagy via ULK1 phosphorylation 43 , 44 . These findings led us to examine whether LD accumulation by ARK1C3 depends on autophagy.…”
Section: Discussionmentioning
confidence: 99%